2017
DOI: 10.3892/br.2017.843
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of atherosclerosis

Abstract: Atherosclerosis is a significant cause of morbidity and mortality globally. Many animal models have been developed to study atherosclerosis, and permit experimental conditions, diet and environmental risk factors to be carefully controlled. Pathophysiological changes can be produced using genetic or pharmacological means to study the harmful consequences of different interventions. Experiments using such models have elucidated its molecular and pathophysiological mechanisms, and provided platforms for pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 101 publications
0
32
0
Order By: Relevance
“…The poor reputation of dietary cholesterol traces back to its supposed promoting role in the development of atherosclerosis [ 1 ]. However, the impact of dietary cholesterol on atherosclerosis has apparently been largely overestimated [ 2 , 3 ] and more recent recommendations for cardio-protective diets do not include the previously suggested radical reduction of cholesterol intake [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The poor reputation of dietary cholesterol traces back to its supposed promoting role in the development of atherosclerosis [ 1 ]. However, the impact of dietary cholesterol on atherosclerosis has apparently been largely overestimated [ 2 , 3 ] and more recent recommendations for cardio-protective diets do not include the previously suggested radical reduction of cholesterol intake [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models are useful system for studying the mechanisms underlying atherosclerosis [19, 20]. Our study and previous animal studies [16, 18] have shown that RBA or thermal treatment can reduce the plaque size, which is a key step in restenosis following balloon angioplasty.…”
Section: Discussionmentioning
confidence: 62%
“…Since most of the smooth muscle cells that create fibrous cap migrate from the media part of the tissue (Lee et al., 2017), the porosity of the fibrous cap is considered the same as the porosity of media. First, the cluster of 5000 ferroparticles with a diameter range of 100 nm to 2000 nm are released with a uniform initial distribution into the artery in the first time step and their behavior in the presence and absence of the external magnetic field is examined.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation of artery intima results from increased concentration of phospholipids and cholesterol, proliferation of smooth muscle cells, and low-density lipoprotein (Anogeianaki et al., 2011; Bose & Banerjee, 2015; Bozsak et al., 2014; Mirza et al., 2017; Priyadharshini & Ponalagusamy, 2018; Soleimani et al., 2018). The smooth muscle cells contribute to fibrous cap formation and protect the core of inflammation (Lee et al., 2017). The primary consequence of artery inflammation is plaque rupture due to low resistance of the plaques to hemodynamic blood pressure and shear stress (Li et al., 2006).…”
Section: Introductionmentioning
confidence: 99%